Appropriation of maternal mHealth interventions by rural-based healthcare clients who do not own mobile phones: the case of Malawi - Maliwichi, Priscilla (Department of Information Systems, 2025)
Problem statement: mHealth interventions may reduce maternal mortality in low-resource settings, through the provision of maternal healthcare information in hard-to-reach areas of Sub-Saharan Africa. Currently, mHealth interventions are bedevilled by inequalities in mobile phone ownership. For example, in Sub-Saharan Africa, women are 13% less likely to own a mobile phone than their male counterparts. In Malawi, male mobile phone ownership is at 44.9%, while for females is at 37.7%. As a result, some maternal mHealth projects facilitate access to mobile phones for those who do not own mobile phones through infomediaries. Most studies in maternal mHealth focus on maternal healthcare clients who own mobile phones. Only a few studies have investigated how maternal healthcare clients who do not own mobile phones appropriate mHealth interventions. Purpose of the study: This study aims to explain how and why maternal healthcare clients who do not own mobile phones appropriate maternal mHealth interventions. Research methodology: The study used a qualitative research method and an interpretive paradigm. The study used a case of Chipatala Cha Pa Foni a maternal and child health intervention in Malawi. The intervention sends SMS and voice messages to maternal healthcare clients based on their stage of pregnancy. Maternal Healthcare clients can also call the toll-free hotline for maternal health-related advice. A conceptual framework was used as a sensitising tool for data collection. Data was collected using secondary data from the implementing agency and empirical data through semi-structured interviews, focus group discussions, and observations. The study used purposive sampling to sample maternal healthcare clients and mobile phone owners. Snowballing was used to sample key informants from the implementing agency. Data was analysed using deductive thematic data analysis. Key findings: The study found that maternal healthcare clients who do not own mobile phones appropriate maternal mHealth interventions. These maternal healthcare clients are influenced to appropriate maternal mHealth interventions by different stakeholders of maternal health. These stakeholders form a community of purpose, wherein some members are infomediaries. The roles of infomediaries include agents of behaviour change, enabling access to maternal health information and promoting a culture of sharing. The study also found that maternal healthcare clients use different tactics to negotiate usage of the mobile phone inter alia issue-based tactics and accommodating tactics. Originality/contribution: The study contributes to the theory through the conceptual framework, which can be used to study the appropriation of interventions from the perspective of users who do not own prerequisite technologies. The study also proposed several frameworks, which can be used to study infomediaries, communities of purpose, and negotiations in ICT4D. Practically, the study has outlined implications that can assist mHealth designers and implementers regarding how their interventions can be inclusive to all beneficiaries regardless of their mobile phone ownership status. In addition, policymakers working on maternal and child health, as well as public health can use the findings of this study to inform mHealth policies that encourage mHealth designers and implementers to develop interventions that can be accessible to people who rely on shared technologies.